Silicon-carbon negative electrode material and preparation method and application thereof

By designing a silicon carbon anode material with a core-shell structure in the lithium-ion battery negative electrode material, the problems of poor conductivity and volume expansion of silicon materials are solved, and high capacity, long life and good rate performance are achieved, which is suitable for large-scale production.

CN119905532APending Publication Date: 2025-04-29DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311402086.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Pure silicon materials, as the negative electrode material for lithium-ion batteries, have poor conductivity and volume expansion problems, resulting in low cycle life and efficiency.

Method used

A silicon-carbon negative electrode material with a core-shell structure is prepared by hard template method, spray drying and high-temperature pyrolysis. The core is nanosilicon and the shell is a carbon layer. A gap is designed between the core and the shell to buffer volume expansion.

Benefits of technology

It achieves high capacity, long cycle life and good rate performance, improves the volume expansion and cycle stability of the silicon-based negative electrode, and is simple in process and low in cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905532A_ABST
    Figure CN119905532A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon negative electrode material and a preparation method and application thereof. The silicon-carbon negative electrode material has a core-shell structure, the core is nanometer silicon, and the shell is a carbon layer; a gap is formed between the inner core and the shell; the particle size of the inner core is 50-100 nm; and in the silicon-carbon negative electrode material, the mass content of the nano silicon is 50-60wt%. And the prepared lithium ion battery silicon-carbon negative electrode material is cheap in raw material, simple in process, environment-friendly, pollution-free and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a silicon-carbon negative electrode material and a preparation method and application thereof, belonging to the field of electrode materials. Background Art

[0002] With the advantages of high energy density, light weight, long cycle life and no memory effect, lithium-ion batteries are widely used in mobile communication equipment, electric vehicles, drones, laptops and other fields. Currently, commercial lithium-ion batteries mainly use graphite as the negative electrode material, and its theoretical specific capacity is close to the theoretical lithium insertion capacity of graphite (372mAh g -1 ), it is difficult to meet people's requirements for high energy density, and there is an urgent need to develop new lithium-ion battery negative electrode materials to meet the needs of thin and light electronic devices, high theoretical specific capacity and large screen.

[0003] Silicon is considered to be the negative electrode material for the next generation of high energy density lithium-ion batteries, mainly due to its abundant reserves and wide distribution, mature single-element silicon preparation and purification process, and extremely high volumetric capacity (9786mAh / cm 3 ) and mass specific capacity (4200mAh / g) and lower discharge potential (Si average delithiation potential 0.4V vs.Li / Li + ). However, there are some problems that cannot be ignored when using pure silicon materials as negative electrode materials for lithium-ion batteries: first, silicon is a semiconductor with poor conductivity; second, silicon will experience severe volume expansion during the process of lithium insertion and extraction, which will cause the electrode material to gradually pulverize during multiple cycles and lead to structural collapse, which in turn causes problems such as low initial efficiency and cycle life. In order to overcome these problems, the current method of combining carbon materials with silicon is mostly used. Combining the advantages of silicon-based materials and carbon-based materials, as well as micro-materials and nano-materials, a high-capacity, stable silicon-carbon negative electrode material is prepared through a reasonable design of the microstructure. Therefore, the development of a silicon-carbon negative electrode material with simple process, excellent performance and environmental friendliness is an important research direction in the field of lithium-ion batteries. Summary of the invention

[0004] The present invention provides a method for preparing a coated, void-type silicon-carbon negative electrode material by hard template method, spray drying and high-temperature pyrolysis, and obtains a lithium-ion battery silicon-carbon negative electrode material with high capacity, long cycle life and good rate performance, which can effectively improve the defects of large volume expansion and poor cycle stability of silicon-based negative electrodes in the prior art, and is beneficial to improving battery performance; at the same time, the preparation process is simple, the preparation cost is low, and it is suitable for large-scale production

[0005] According to one aspect of the present application, a silicon-carbon negative electrode material is provided, wherein the silicon-carbon negative electrode material has a core-shell structure, wherein the core is nano-silicon and the shell is a carbon layer;

[0006] There is a gap between the inner core and the outer shell;

[0007] The particle size of the core is 50 to 100 nm;

[0008] In the silicon-carbon negative electrode material, the mass content of the nano-silicon is 50-60wt%.

[0009] The shell thickness of the silicon-carbon negative electrode material is 5 to 15 nm;

[0010] The pore size of the silicon-carbon negative electrode material is 1 to 100 nm;

[0011] The void size of the silicon-carbon negative electrode material is 8 to 20 nm.

[0012] According to another aspect of the present application, a method for preparing the above-mentioned silicon-carbon negative electrode material is provided, comprising the following steps:

[0013] (1) Using the co-precipitation method, a layer of calcium carbonate is deposited on the surface of nano-silicon particles as a void template;

[0014] (2) mixing the void template, gelatin, and water, and depositing the mixture to obtain a void template coated with gelatin;

[0015] (3) Mixing the gelatin-coated void template with carbon nanotubes and conductive carbon black, drying, calcining, and etching to obtain the silicon-carbon negative electrode material.

[0016] The coprecipitation method comprises the following steps: mixing nano silicon and calcium carbonate in a mass ratio of 1:3 to 1:5 in deionized water, ultrasonicating for 2 hours, and fully stirring for 12 hours.

[0017] The particle size of the nano silicon particles is 50-100 nm.

[0018] The mass ratio of the void template to the gelatin is 1:1 to 1:3;

[0019] The mass ratio of the void template to the water is 1:300 to 1:500;

[0020] The mass ratio of the void template to the carbon nanotube is 1:1 to 1:3;

[0021] The mass ratio of the void template to the conductive carbon black is 1:1 to 1:3;

[0022] The drying temperature is 120-180°C;

[0023] The drying is spray drying, and the feed rate of the spray drying is 3 ml / min.

[0024] The calcination temperature is 450-900°C;

[0025] The calcination time is 1 to 3 hours;

[0026] The calcination atmosphere is an inert gas atmosphere;

[0027] The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

[0028] The etching is acid etching;

[0029] The acid etching time is 10 to 30 hours;

[0030] The acid used in the acid etching is at least one selected from hydrochloric acid, sulfuric acid and hydrofluoric acid.

[0031] Specifically, the steps include:

[0032] (1) A layer of CaCO3 is deposited on the Si surface by co-precipitation method as a void template;

[0033] (2) dispersing Si@CaCO3 powder and gelatin in a deionized water solution, depositing a gelatin polymer layer on the surface of the Si@CaCO3 powder, adding carbon nanotubes and conductive carbon black, and ultrasonically stirring the mixed solution until it is completely dispersed;

[0034] (3) spray drying the dispersed Si@CaCO3@GT solution to obtain silicon-carbon precursor powder;

[0035] (4) calcining the precursor powder in a tube furnace at high temperature with argon to obtain a carbon-coated Si@CaCO3 / GC material;

[0036] (5) The Si@CaCO3@GC material is etched in 10% dilute hydrochloric acid to obtain Si / Void / GC with void space.

[0037] Among them, GT is gelatin;

[0038] GC is gelatin derived carbon or carbon layer.

[0039] According to another aspect of the present application, there is provided an application of the above-mentioned silicon-carbon negative electrode material for lithium-ion batteries.

[0040] The beneficial effects of this application include:

[0041] 1. CaCO3 as a template has many advantages such as large specific surface area, stable properties, controllable structure, green and non-toxic, easy to digest, etc. It can be quickly eliminated by etching with dilute hydrochloric acid, avoiding the use of highly harmful HF acid and having better safety.

[0042] 2. After the CaCO3 template is removed by dilute hydrochloric acid etching, the volume expansion problem of silicon can be effectively buffered due to the suitable void space between the silicon core and the carbon shell, thereby improving the cycle stability and cycle life of the battery.

[0043] 3. As a water-soluble polymer, gelatin has abundant carboxyl (-COOH) and amino (-NH2) groups and has good film-forming and adhesive properties. These properties enable gelatin to form a uniform coating on silicon particles even at low doses and firmly fix silicon on copper foil, thereby ensuring a high silicon content. After controlled pyrolysis, gelatin is converted into a continuous N, O-doped carbon network, forming a double interface between Si and the current collector, improving conductivity and mechanical flexibility; on the other hand, it acts as a buffer layer to alleviate the volume expansion problem of silicon, achieving high-capacity and long-life electrochemical performance.

[0044] 4. The silicon-carbon negative electrode material prepared by spray drying has a higher tap density, can maintain structural stability during long cycles, and improve cycle life.

[0045] 5. The prepared lithium-ion battery negative electrode material has cheap raw materials, simple process, environmentally friendly and pollution-free, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The XRD spectrum of the Si / Void / GC silicon-carbon negative electrode material prepared in Example 1;

[0047] Figure 2 Thermogravimetric spectrum of the Si / Void / GC silicon-carbon negative electrode material prepared in Example 1;

[0048] Figure 3 The Si / Void / GC silicon-carbon negative electrode material prepared in Example 1 was heated to 0.2Ag. -1 The first cycle charge and discharge curve under

[0049] Figure 4 The Si / Void / GC silicon-carbon negative electrode material prepared in Example 1 was heated to 0.2Ag. -1 Lower cycle performance curve;

[0050] Figure 5 This is the rate performance curve of the Si / Void / GC silicon-carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0051] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0052] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0053] Example 1

[0054] (1) A layer of CaCO3 was deposited on the Si surface by co-precipitation as a void template: nano-silicon: calcium carbonate was mixed in deionized water at a mass ratio of 1:3-1:5, ultrasonicated for 2 h, and stirred for 12 h;

[0055] (2) 1 g Si@CaCO3 powder and 0.25 g gelatin were dispersed in 300 mL deionized water solution, a gelatin polymer layer was deposited on the surface of Si@CaCO3 powder, 0.25 g carbon nanotubes and 0.25 g conductive carbon black were added, and the mixed solution was sonicated and stirred until it was completely dispersed;

[0056] (3) The dispersed Si@CaCO3@GT solution is spray dried at an inlet temperature of 120°C to obtain a silicon-carbon precursor powder;

[0057] (4) calcining the precursor powder in an argon-filled tube furnace at a carbonization temperature of 450°C for 3 h to obtain a carbon-coated Si@CaCO3 / GC material;

[0058] (5) The Si@CaCO3@GC material was etched in 10% dilute hydrochloric acid for 20 h to obtain a Si / Void / GC silicon-carbon negative electrode material with void space.

[0059] Figure 1 This is the XRD spectrum of the Si / Void / GC silicon-carbon negative electrode material prepared in this example. It can be seen from the figure that there are only two phases, Si and C, in the Si / Void / GC composite material, and the characteristic peak of Si matches well with pure nano-silicon, and no impurity peaks appear, indicating that the synthesized material is of high purity;

[0060] Figure 2 This is the thermogravimetric spectrum of the Si / Void / GC silicon-carbon negative electrode material prepared in this embodiment. It can be seen from the figure that the silicon content in the composite material is 50%, which is relatively high;

[0061] Figure 3 The Si / Void / GC silicon-carbon negative electrode material prepared in this embodiment is 0.2A g -1 The first cycle charge and discharge curve below; it can be seen from the figure that thanks to the high silicon content in the prepared silicon-carbon negative electrode material, the first cycle discharge specific capacity is relatively high, and the discharge specific capacity reaches 2000mAh / g.

[0062] Figure 4 The Si / Void / GC silicon-carbon negative electrode material prepared in this embodiment is 0.2A g -1Lower cycle performance curve; it can be seen from the figure that thanks to the sufficient void space of the prepared silicon-carbon negative electrode material, the serious silicon volume expansion problem during the cycle can be buffered, and a silicon-carbon negative electrode material with excellent cycle stability can be obtained.

[0063] Figure 5 This is the rate performance curve of the Si / Void / GC silicon-carbon negative electrode material prepared in this embodiment. It can be seen from the figure that thanks to the sufficient void space of the prepared silicon-carbon negative electrode material, the serious silicon volume expansion problem during the cycle can be buffered, and a silicon-carbon negative electrode material with excellent cycle stability can be obtained.

[0064] Example 2

[0065] (1) A layer of CaCO3 was deposited on the Si surface by co-precipitation as a void template: nano-silicon: calcium carbonate was mixed in deionized water at a mass ratio of 1:3-1:5, ultrasonicated for 2 h, and stirred for 12 h;

[0066] (2) 1 g Si@CaCO3 powder and 0.25 g gelatin were dispersed in 300 mL deionized water solution, a gelatin polymer layer was deposited on the surface of Si@CaCO3 powder, 0.25 g carbon nanotubes and 0.25 g conductive carbon black were added, and the mixed solution was sonicated and stirred until it was completely dispersed;

[0067] (3) The dispersed Si@CaCO3@GT solution is spray dried at an inlet temperature of 140°C to obtain a silicon-carbon precursor powder;

[0068] (4) calcining the precursor powder in an argon-filled tube furnace at a carbonization temperature of 600°C for 3 h to obtain a carbon-coated Si@CaCO3 / GC material;

[0069] (5) The Si@CaCO3@GC material was etched in 10% dilute hydrochloric acid for 30 h to obtain a Si / Void / GC silicon-carbon negative electrode material with void space.

[0070] The material characterization results are similar to those in Example 1.

[0071] Example 3

[0072] (1) A layer of CaCO3 was deposited on the Si surface by co-precipitation as a void template: nano-silicon: calcium carbonate was mixed in deionized water at a mass ratio of 1:3-1:5, ultrasonicated for 2 h, and stirred for 12 h;

[0073] (2) 1 g Si@CaCO3 powder and 0.25 g gelatin were dispersed in 399 mL deionized water solution, a gelatin polymer layer was deposited on the surface of Si@CaCO3 powder, 0.25 g carbon nanotubes and 0.25 g conductive carbon black were added, and the mixed solution was ultrasonically stirred until it was completely dispersed;

[0074] (3) The dispersed Si@CaCO3@GT solution is spray dried at an inlet temperature of 160°C to obtain a silicon-carbon precursor powder;

[0075] (4) calcining the precursor powder in an argon-filled tube furnace at a carbonization temperature of 900°C for 3 h to obtain a carbon-coated Si@CaCO3 / GC material;

[0076] (5) The Si@CaCO3@GC material was etched in 10% dilute hydrochloric acid for 30 h to obtain a Si / Void / GC silicon-carbon negative electrode material with void space.

[0077] The material characterization results are similar to those in Example 1.

[0078] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A silicon-carbon negative electrode material, characterized in that The silicon-carbon negative electrode material has a core-shell structure, the core is nano-silicon, the shell is a carbon layer; there is a gap between the core and the shell; The particle size of the core is 50 to 100 nm; In the silicon-carbon negative electrode material, the mass content of the nano-silicon is 50-60wt%.

2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The shell thickness of the silicon-carbon negative electrode material is 5 to 15 nm; The pore size of the silicon-carbon negative electrode material is 1 to 100 nm; The void size of the silicon-carbon negative electrode material is 8 to 20 nm.

3. A method for preparing the silicon-carbon negative electrode material according to any one of claims 1 or 2, characterized in that: The following steps are involved: (1) Using the co-precipitation method, a layer of calcium carbonate is deposited on the surface of nano-silicon particles as a void template; (2) mixing the void template, gelatin, and water, and depositing the mixture to obtain a void template coated with gelatin; (3) Mixing the gelatin-coated void template with carbon nanotubes and conductive carbon black, drying, calcining, and etching to obtain the silicon-carbon negative electrode material.

4. The preparation method according to claim 3, characterized in that: The particle size of the nano silicon particles is 50-100 nm.

5. The preparation method according to claim 3, characterized in that: The mass ratio of the void template to the gelatin is 1:1 to 1:3; The mass ratio of the void template to the water is 1:300 to 1:

500.

6. The preparation method according to claim 3, characterized in that: The mass ratio of the void template to the carbon nanotube is 1:1 to 1:3; The mass ratio of the void template to the conductive carbon black is 1:1 to 1:

3.

7. The preparation method according to claim 3, characterized in that: The drying is spray drying; The drying temperature is 120-180°C.

8. The preparation method according to claim 3, characterized in that: The calcination temperature is 450-900°C; The calcination time is 1 to 3 hours; The calcination atmosphere is an inert gas atmosphere; The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

9. The preparation method according to claim 3, characterized in that: The etching is acid etching; The acid etching time is 10 to 30 hours; The acid used in the acid etching is at least one selected from hydrochloric acid, sulfuric acid and hydrofluoric acid.

10. An application of the silicon-carbon negative electrode material according to any one of claims 1 or 2, characterized in that: For lithium-ion batteries.

Citation Information

Patent Citations

  • Silicon-carbon composite material and preparation method thereof, and lithium ion battery

    CN103337613A

  • Silicon-carbon composite material and preparation method thereof and application thereof in lithium ion battery

    CN106159213A

  • Silicon carbon negative electrode material, preparation method thereof and lithium ion battery

    CN109461890A

  • Negative electrode material of lithium ion battery and manufacturing method thereof

    CN110459757A